When smokers move out and non-smokers move in: residential thirdhand smoke pollution and exposure. Issue 1 (30th October 2010) - Matt, Georg E; Quintana, Penelope J E; Zakarian, Joy M; Fortmann, Addie L; Chatfield, Dale A; Hoh, Eunha; Uribe, Anna M; Hovell, Melbourne F
Abstract : Background: This study examined whether thirdhand smoke (THS) persists in smokers' homes after they move out and non-smokers move in, and whether new non-smoking residents are exposed to THS in these homes. Methods: The homes of 100 smokers and 50 non-smokers were visited before the residents moved out. Dust, surfaces, air and participants' fingers were measured for nicotine and children's urine samples were analysed for cotinine. The new residents who moved into these homes were recruited if they were non-smokers. Dust, surfaces, air and new residents' fingers were examined for nicotine in 25 former smoker and 16 former non-smoker homes. A urine sample was collected from the youngest resident. Results: Smoker homes' dust, surface and air nicotine levels decreased after the change of occupancy (p<0.001); however dust and surfaces showed higher contamination levels in former smoker homes than former non-smoker homes (p<0.05). Non-smoking participants' finger nicotine was higher in former smoker homes compared to former non-smoker homes (p<0.05). Finger nicotine levels among non-smokers living in former smoker homes were significantly correlated with dust and surface nicotine and urine cotinine. Conclusions: These findings indicate that THS accumulates in smokers' homes and persists when smokers move out even after homes remain vacant for 2 months and are cleaned and prepared for new residents. When non-smokers move into homes formerly occupied by smokers, they encounter indoor environments with THS polluted surfaces and dust. Results suggest that non-smokers living in former smoker homes are exposed to THS in dust and on surfaces.